Improved crystallinity, optical and electrical properties of ZnSe–Se2O5 films through O+ implantation. (August 2022) - Gupta, Tripti; Chauhan, R.P.
Abstract: Modification of optical and electrical properties of the material at the nano level is advantageous for applications like photodetectors, window layers, and sensors. This work put forth the modification of ZnSe–Se2 O5 film properties through O + ions implantation at 60 keV energy with different fluences. After treatment, comprehensive characterizations of implanted films are executed to investigate their structural, optical, and electrical properties. The obtained experimental results are reinforced by SRIM-TRIM simulations to interpret the nature and course of events that occur during implantation. Meticulous investigations of implanted films affirm that O + ion implantation at a fluence of 7 × 10 15 ions/cm 2 yields the best results exhibiting crystalline nature, narrow optical bandgap, high refractive index, and excellent electrical conductivity due to implantation induced ionization and damages produced in the films. Thus, our study stipulates that implantation of O + ions into films enhances electrical conductivity which is crucial for advanced applications, such as sensing toxic gases and optoelectronics. Highlights: Modification of polycrystalline ZnSe–Se2 O5 films using O + beam implantation is demonstrated. Experimental results are reinforced by SRIM-TRIM to interpret the nature and course of events occurring during implantation. The optical bandgap is reduced with increase in implantation fluence. Enhancement in conductivity provided new insights to the utilize semiconductors in fabricating nano-electronic devices.